2006
DOI: 10.1136/hrt.2005.083592
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler velocity is superior to displacement and strain mapping in predicting left ventricular reverse remodelling response after cardiac resynchronisation therapy

Abstract: Tissue velocity parameters of systolic asynchrony are superior to those of displacement and strain mapping in predicting LV reverse remodelling response after CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 34 publications
1
63
0
2
Order By: Relevance
“…Relative movements of the myocardial wall with reference to the Doppler probe are analyzed, whereas strain imaging or MRI-based velocities need no reference outside the myocardium and contain only a single velocity direction. This might partly explain why Doppler-derived systolic long-axis velocities can predict the prognosis after CRT better than systolic long-axis strain (19,20). In agreement with these considerations and our results, a recent study in dogs showed that either systolic circumferential strain or diastolic long-axis strain was a better predictor of improved LV function after CRT compared to systolic long-axis strain (21).…”
Section: Discussionmentioning
confidence: 99%
“…Relative movements of the myocardial wall with reference to the Doppler probe are analyzed, whereas strain imaging or MRI-based velocities need no reference outside the myocardium and contain only a single velocity direction. This might partly explain why Doppler-derived systolic long-axis velocities can predict the prognosis after CRT better than systolic long-axis strain (19,20). In agreement with these considerations and our results, a recent study in dogs showed that either systolic circumferential strain or diastolic long-axis strain was a better predictor of improved LV function after CRT compared to systolic long-axis strain (21).…”
Section: Discussionmentioning
confidence: 99%
“…Using 2-dimensional speckle tracking, a delay >130ms in time to peak systolic radial strain among 6 mid segments in parasternal short axis view predicted increase in EF >15% at 8 months after CRT (16). However, Yu and colleagues (17) reported that standard deviation in time to peak systolic TDI-derived strain in 12 segments did not predict the response to CRT.…”
Section: Strain Imagingmentioning
confidence: 97%
“…Several methods of quantifying deviations from synchronous movement have been proposed. The most common method was proposed by Yu, et al and involves calculating the standard deviation of the times to peak systolic velocity among the 12 regions of interest (SD-TVI) (Yu et al 2005;Yu et al 2006). A cut-off of 32 ms has been used to indicate clinically significant dyssynchrony (Yu et al 2005).…”
Section: Longitudinal Motionmentioning
confidence: 99%